Listeria monocytogenes endophthalmitis – case report and review of risk factors and treatment outcomes. Issue 1 (December 2016) - Bajor, Anna; Luhr, Anke; Brockmann, Dorothee; Suerbaum, Sebastian; Framme, Carsten; Sedlacek, Ludwig
Abstract Background The majority of cases of endophthalmitis are caused by exogenous pathogens; only 5–10 % are of endogenous origin. One cause of these rare cases of endogenous endophthalmitis isListeria monocytogenes . Twenty-six cases of endophthalmitis due to this pathogen have been published over the last twenty years. The aim of this review is to summarize the main risk factors and common clinical findings of endogenous endophthalmitis due toListeria monocytogenes . Case presentation We report on a 62-year-old female presenting with a sterile hypopyon iritis with secondary glaucoma and an underlying rheumatoid disease. In microbiological analysis we identifiedListeria monocytogenes . Further we searched through all published cases for typical signs, risk factors, details of medical and surgical treatment and outcome of endogenous endophthalmitis due to this rare pathogen. Ocular symptoms in almost all of these published cases included pain, redness of the eye, and decreased vision. Main clinical features included elevated intraocular pressure and fibrinous anterior chamber reaction, as well as a dark hypopyon. While the infection is typically spread endogenously, neither an exogenous nor endogenous source of infection could be identified in most cases. Immunocompromised patients are at higher risk of being infected than immunocompetent patients. The clinical course of endophthalmitis caused byListeria monocytogenes had different visual outcomes. In some cases, the infection led to enucleation, blindness, or strong visual loss, whereas most patients showed a tendency of visual improvement during therapy. Conclusion Early diagnosis and treatment initiation are crucial factors in the outcome of endogenous endophthalmitis caused byListeria monocytogenes . This possible differential diagnosis should be kept in mind while treating patients with presumable sterile hypopyon and anterior uveitis having a high intraocular pressure. A bacterial source should be considered with a prompt initiation of systemic antibiotic treatment, mainly in immunocompromised patients, who develop endogenous anterior uveitis. An appropriate microbiological sampling is essential to detect atypical microorganisms and to choose an effective antibiotic treatment.